Competency Certification Test: Students' Understanding of Theory and Practice at the Internship Site - Kusairi, Kusairi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2026)
This study evaluates the effectiveness of competency certification tests in reflecting vocational education students' understanding of the integration of theory and practice during internship programs. Vocational education focuses on developing practical skills that are relevant to the needs of industry and the job market, and preparing graduates to be ready to compete in a dynamic global market. However, there is a gap between the theoretical material taught and the practice in the field, which makes it difficult for students to apply knowledge optimally. The competency certification test acts as a measuring tool that assesses students' mastery of practical skills and work readiness objectively. This study used a qualitative method with a case study approach through interviews, observations, and documentation of certification results.